Innate immune adaptor TRIF deficiency accelerates disease progression of ALS mice with accumulation of aberrantly activated astrocytes. Issue 12 (December 2018) - Komine, Okiru; Yamashita, Hirofumi; Fujimori-Tonou, Noriko; Koike, Masato; Jin, Shijie; Moriwaki, Yasuhiro; Endo, Fumito; Watanabe, Seiji; Uematsu, Satoshi; Akira, Shizuo; Uchiyama, Yasuo; Takahashi, Ryosuke; et al.
Abstract There is compelling evidence that glial-immune interactions contribute to the progression of neurodegenerative diseases. The adaptive immune response has been implicated in disease processes of amyotrophic lateral sclerosis (ALS), but it remains unknown if innate immune signaling also contributes to ALS progression. Here we report that deficiency of the innate immune adaptor TIR domain-containing adaptor inducing interferon-β (TRIF), which is essential for certain Toll-like receptor (TLR) signaling cascades, significantly shortens survival time and accelerates disease progression of ALS mice. While myeloid differentiation factor 88 (MyD88) is also a crucial adaptor for most TLR signaling pathways, MyD88 deficiency had only a marginal impact on disease course. Moreover, TRIF deficiency reduced the number of natural killer (NK), NK-T-lymphocytes, and CD8-T cells infiltrating into the spinal cord of ALS mice, but experimental modulation of these populations did not substantially influence survival time. Instead, we found that aberrantly activated astrocytes expressing Mac2, p62, and apoptotic markers were accumulated in the lesions of TRIF-deficient ALS mice, and that the number of aberrantly activated astrocytes was negatively correlated with survival time. These findings suggest that TRIF pathway plays an important role in protecting a microenvironment surrounding motor neurons by eliminating aberrantly activated astrocytes.